TELEWORKING WITH FAMILIES OF CHILDREN WITH DISABILITIES - Glamočak, Sandra (PONS - medicinski časopis, 2022)
The coronary virus pandemic has led to great changes in the lives of a large number of families and as such has imposed new patterns of behavior, which have required a series of daily adaptations to the new situation. The impact of the pandemic and the adherence to all prescribed epidemiological measures in order to combat coronavirus infection, undoubtedly had a great impact on the families of children with disabilities because there was a suspension of work with children. For this reason, all forms of direct support to children with disabilities and their families have been disabled, and new forms of support in the virtual environment have been introduced instead. Teleworking involves providing support to families of children with disabilities through video conferencing technology. Given the availability and access to technology, access to services through teleintervention is an attractive and flexible option for families, especially during challenging situations of this type.